Art Fairs as a Medium for Branding Young and Emerging Artists: The Case of Frieze London. Issue 3 (26th May 2016) - Lee, Soo Hee; Lee, Jin Woo
ABSTRACT: While previous researchers have attempted to explain the uncertain quality of visual arts with reference to branding theory, they have overlooked the role of art fairs. Socio-cultural approaches to branding allow us to explore the function of intermediaries in valuing contemporary arts. This article aims to analyze the role of art fairs in the process of branding young and emerging artists. In particular, a prestigious art fair, Frieze London, serves as an instrumental case study for developing a systematic understanding of art fairs in terms of valuing and branding contemporary art.